AN ANALYSIS ON THE KIND OF TASKS FOUND IN ENGLISH MODULE FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Yani Awalia Indah; Ayusa Muhasonah (ENGLISH, 2018)
This research was applied descriptive qualitative and used content analysis design. The researcher took checklist table as the instrument. The purpose of the study was to analyze and classify the type of tasks in Modul Bahasa Inggris created by Bogor English teacher organization used for seventh grades in Junior High School. Based on Willis (2000) taxonomy of task types, it found that the module cover task types such as Sharing Personal Experience (40.32%) tasks were  the  most  frequent  and  Listing  (14.52%),  Problem  Solving  (14.52%), Ordering  and  Sorting  (11.29%),  Comparing  (11.29%),  and  Creative  tasks (8.06%), respectively, were the least common tasks types presented in Modul Bahasa Inggris created by Bogor English teacher organization. This module is good because almost of the types by Willis (2000) taxonomy of task types was covered by this module. The results of this study hope that the English teachers to be more aware of different task types which are important to learning process. For developers in order to develop and enrich the presented English Learning teaching materials with more communicative tasks.